Sarcomatoid carcinoma represents a complete phenotype with various pathways of epithelial mesenchymal transition. Issue 7 (26th March 2013) - Sung, Chang Ohk; Choi, Hannah; Lee, Keun-Woo; Kim, Seok-Hyung
Abstract : Aims: Sarcomatoid carcinoma (SC) is considered to be a result of the sarcomatoid change of epithelial carcinoma. However, epithelial–mesenchymal transition (EMT) in SC has been insufficiently studied. Methods: We evaluated the expression patterns of EMT-related phenotypic markers with transcription factors in 27 SCs originating from various organs, and we investigated the phenotypic characteristics of SCs classified as complete, incomplete or wild-type. We further analysed correlations between EMT-related phenotype markers and transcription factors. Results: Epithelial markers (E-cadherin, claudin-3 and claudin-4) were consistently down-regulated, whereas mesenchymal markers (S100A4, α-smooth muscle actin (SMA), vimentin, PDGFRα and β-catenin) were variously expressed except for vimentin. EMT-related transcription factors (SIP1, Snail1, Slug, Twist1, ZEP1 and Oct-4) also showed various expression patterns. The expression patterns of phenotypic markers showed that most SCs (22/27, 81.5%, 95% CI 65.8 to 97.1%) had complete EMT phenotypes, whereas the remaining 5 (18.5%, 95% CI 2.8 to 24.1%) were of incomplete type. Unsupervised hierarchical clustering analysis revealed that SCs were clustered into several subgroups by EMT-related protein expression pattern. Twist1 positivity was significantly concordant with α-SMA positivity (κ value: 0.908; 95% CI 0.73 to 1.00, p<0.001, adjusted p<0.001). The EMT phenotypes of SC were simple, with complete phenotype being the predominant form, and the morphological changes of the SCs were also relevant in terms of EMT. Conclusions: SC seems to be an irreversible, permanent change in the EMT phenomenon, with complete EMT phenotypes and various EMT-related pathways being involved in SC.